PENGEMBANGAN SOAL TES PENALARAN TINGGI BERBASIS KOMPUTER PADA BAHASAN TRIGONOMETRI SMA - Marina Kuswardani; I Nyoman Arcana (UNION: Jurnal Ilmiah Pendidikan Matematika, 2017)
This study aims to (1) Developing the higer oreder thinking skills test on computer based in the subject of trigonometric SMA. (2) Knowing the feasibility of a higer oreder thinking skills tests computer based made on the subject of trigonometric SMA. This research is a research and development (Research & Development). The development method used in this study follows a simple development procedure suggested by Borg and Gall consisting of five steps: (1) Product analysis to be developed, (2) initial product development, (3) Expert Validation and product revision, (4) ) Limited field trials and product revisions, (5) Main-scale field trials and end products. The results of this study is a computer-based test entitled: "Computer Based Test Problems On High Trigonometric Discussion" which is packaged in the form of Comapct Disk (CD). The computer-based tests were tested limited trial of 30 students and a major trials of 34 SMA N 10 Yogyakarta. Problem-based computer test has met the validity, reliability, objectivity, praktibilitas, and economical. Validation results show a computer-based test is worth using. This is supported by: average grain matter about 4.80 (very good) and average media expert 4,76 (very good) and student questionnaire score 39,03 (very good. Â Research suggestions, the product should be used by students as an exercise in computer based reasoning.Â